2021
DOI: 10.1002/jsfa.11419
|View full text |Cite
|
Sign up to set email alerts
|

High and low oxalate content in spinach: an investigation of accumulation patterns

Abstract: BACKGROUND Oxalic acid is a common antinutrient in the human diet, found in large quantities in spinach. However, spinach is highly regarded by vegetable producers because of its nutritional content and economic value. One of the primary purposes of spinach‐breeding programs is to improve the nutritional value of spinach by adjusting oxalate accumulation. Knowledge of the biosynthetic patterns of oxalic acid, and its different forms, is important for a better understanding of this process. RESULTS We found thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…23 Recently, by investigating the accumulation patterns of oxalic acid in spinach varieties with different oxalic acid contents, it was found that ascorbic acid can significantly increase the proportion of insoluble oxalate to total oxalic acid but contributes little to oxalate biosynthesis. 35 These contradictory results suggest that ascorbic acid may have different roles in oxalic acid biosynthesis in different plant species. Direct molecular genetic evidence is required to further support the role of ascorbic acid in oxalate biosynthesis.…”
Section: ■ Distribution Of and Biosynthesis Of Oxalic Acid In Plantsmentioning
confidence: 99%
See 1 more Smart Citation
“…23 Recently, by investigating the accumulation patterns of oxalic acid in spinach varieties with different oxalic acid contents, it was found that ascorbic acid can significantly increase the proportion of insoluble oxalate to total oxalic acid but contributes little to oxalate biosynthesis. 35 These contradictory results suggest that ascorbic acid may have different roles in oxalic acid biosynthesis in different plant species. Direct molecular genetic evidence is required to further support the role of ascorbic acid in oxalate biosynthesis.…”
Section: ■ Distribution Of and Biosynthesis Of Oxalic Acid In Plantsmentioning
confidence: 99%
“… By contrast, repressed expression of l -galactono-1,4-lactone dehydrogenase (GLDH) gene encoding enzyme that catalyzes the last step of the ascorbic acid synthesis pathway significantly reduced the ascorbic acid content in rice but did not decrease the oxalic acid content . Recently, by investigating the accumulation patterns of oxalic acid in spinach varieties with different oxalic acid contents, it was found that ascorbic acid can significantly increase the proportion of insoluble oxalate to total oxalic acid but contributes little to oxalate biosynthesis . These contradictory results suggest that ascorbic acid may have different roles in oxalic acid biosynthesis in different plant species.…”
Section: Distribution Of and Biosynthesis Of Oxalic Acid In Plantsmentioning
confidence: 99%